Synthesis and electronic properties of nitrogen-doped π-extended polycyclic aromatic dicarboximides with multiple redox processes - Alonso-Navarro, Matías J.; Harbuzaru, Alexandra; Martínez-Fernández, Marcos; Pérez Camero, Paula; López-Navarrete, Juan Teodomiro; Ramos, M. Mar; Ponce-Ortiz, Rocío; Segura, José L. (Royal Society of chemistry, 2021)
In this work, a series of nitrogen-doped polycyclic aromatic mono and dicarboximides was designed, and their synthesis is reported by an innovative synthetic procedure that avoids metal-based cross-coupling reactions. A combined theoretical, electrochemical, optical spectroscopy and material characterization study allows the investigation of the interplay of different effects such as (i) the type of solubilizing chain, (ii) the all-acceptor vs. donor–acceptor nature of the novel systems, and (iii) the molecular ordering, on the ability to stabilize multiple charges and on the OTFT device response characteristics. The amphoteric redox behavior of some of the novel systems allow to obtain ambipolar mobilities while the electron mobility values of the three all-acceptor systems can be rationalized in terms of supramolecular aggregation and enhanced film-forming ability.
Keywords: Espectroscopía; Optical spectroscopy; Redox processes